Paulus se hantering van eksterne stressors, en die verhouding tussen identiteit, etiek en etos in Filippense - Franken, Chris (HTS teologiese studies, 2012)
Paul coping with external stressors: Exploring the relationship between identity, ethics and ethos in Philippians. Stress is one of the most prominent sicknesses of the third millennium. This article used the external categories of stress and the heuristic ethical indicators (identity, ethics and ethos) to determine why Paul lived with joy despite of his stressful circumstances. As for people sharing the same Christian identity of the first followers of Jesus, this should be of real significance to the situation of stress in the third millennium.